2021
DOI: 10.1093/ons/opab088
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Giant Anterior Skull Base Encephalocele Containing Intralesional Eloquent Brain: Technical Note

Abstract: BACKGROUND Encephaloceles are herniations of intracranial neural tissue and meninges through defects in the skull. Basal encephaloceles are rare anterior skull base defects incident in 1 in 35,000 live births. Sphenoethmoidal encephaloceles are even more uncommon, with an incidence of 1 in 700,000 live births. Anterior skull base encephaloceles may be life-threatening in infants, presenting as airway obstruction and respiratory compromise. They can also present with cerebrospinal fluid (CSF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Meningoencephalocele occurs mainly in infants with a very low incidence and is extremely rare in adults [6]. Zada et al first reported a case about chronic aspirationinduced pneumonitis caused by spontaneous ethmoid sinus meningocele with CSF rhinorrhea, and indicated that increased diagnostic complexity associated with pulmonary complications led to unnecessary intervention and treatment delays [7].…”
Section: Discussionmentioning
confidence: 99%
“…Meningoencephalocele occurs mainly in infants with a very low incidence and is extremely rare in adults [6]. Zada et al first reported a case about chronic aspirationinduced pneumonitis caused by spontaneous ethmoid sinus meningocele with CSF rhinorrhea, and indicated that increased diagnostic complexity associated with pulmonary complications led to unnecessary intervention and treatment delays [7].…”
Section: Discussionmentioning
confidence: 99%